2012
DOI: 10.1155/2012/716739
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Children with Febrile Urinary Tract Infection: Bottom-Up, Top-Down, or None of the Above?

Abstract: The proper algorithm for the radiographic evaluation of children with febrile urinary tract infection (FUTI) is hotly debated. Three studies are commonly administered: renal-bladder ultrasound (RUS), voiding cystourethrogram (VCUG), and dimercapto-succinic acid (DMSA) scan. However, the order in which these tests are obtained depends on the methodology followed: bottom-up or top-down. Each strategy carries advantages and disadvantages, and some groups now advocate even less of a workup (none of the above) due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
(75 reference statements)
0
18
0
2
Order By: Relevance
“…Only those with parenchymal involvement detected on acute-phase DMSA imaging are referred for a VCUG in addition to delayed DMSA (≥6 months after fUTI) to evaluate permanent scarring. [13,14] Although the diagnosis of dilating VUR is missed in a small subgroup of children at risk of developing severe kidney damage, some studies have supported this strategy having high sensitivity, specificity, and negative predictive value for predicting clinically significant VUR. [15][16][17] However, conclusions from two meta-analyses have demonstrated that acute-phase DMSA scintigraphy for predicting VUR was not accurate enough in children with fUTI.…”
Section: Discussionmentioning
confidence: 99%
“…Only those with parenchymal involvement detected on acute-phase DMSA imaging are referred for a VCUG in addition to delayed DMSA (≥6 months after fUTI) to evaluate permanent scarring. [13,14] Although the diagnosis of dilating VUR is missed in a small subgroup of children at risk of developing severe kidney damage, some studies have supported this strategy having high sensitivity, specificity, and negative predictive value for predicting clinically significant VUR. [15][16][17] However, conclusions from two meta-analyses have demonstrated that acute-phase DMSA scintigraphy for predicting VUR was not accurate enough in children with fUTI.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that acquired kidney damage is related more to the UTI than to the VUR. [4][5][6] Under the 2003 SAP algorithm, no VUR or scarring diagnosis was missed. With the 2015 recommendations, 4 VURs (1 grade II, 2 grade III and 1 grade IV) and 2 cases of small scarring would have gone undiagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a marked variability as regards sensitivity and specificity for the detection of abnormalities, as well as a great difference in health-related costs and radiation exposure. [5][6][7] In Argentina, the algorithm by the Argentine Society of Pediatrics (SAP) in 2003, recommending an ultrasound, a voiding cystourethrography (VCUG) and a late dimercaptosuccinic acid (DMSA) scintigraphy for all children ≤ 2 after the first febrile UTI, was reviewed. 8 In the most recent consensus by SAP in 2015, it was decided that, after the first febrile UTI with normal kidney and bladder ultrasound scans, the VCUG would be restricted to children ≤ 1 and the DMSA to patients with VUR, six months after the UTI.…”
Section: Introductionmentioning
confidence: 99%
“…Megalin and cubilin are cooperating receptors essential to the proximal tubule endocytic uptake of proteins from the glomerular filtrate in the proximal tubule. Tc-DMSA renal scan is still considered as the gold standard for diagnosing acute pyelonephritis and chronic lesions like renal scars and is recommended in many investigative algorithms in pediatric practice [10,11,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%